2021
DOI: 10.3390/app11135880
|View full text |Cite
|
Sign up to set email alerts
|

BioECG: Improving ECG Biometrics with Deep Learning and Enhanced Datasets

Abstract: Nowadays, Deep Learning tools have been widely applied in biometrics. Electrocardiogram (ECG) biometrics is not the exception. However, the algorithm performances rely heavily on a representative dataset for training. ECGs suffer constant temporal variations, and it is even more relevant to collect databases that can represent these conditions. Nonetheless, the restriction in database publications obstructs further research on this topic. This work was developed with the help of a database that represents pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Earlier research papers have reported that the CNN, LSTM, and CNN-LSTM architectures for ECG authentication were able to achieve a classification accuracy of over 90% [ 35 ]. Although none of the proposed models offer a direct authentication approach that can be implemented without post-processing after classification, supervised DNN-based models, like classifiers, are commonly employed for authentication [ 36 ].…”
Section: Related Workmentioning
confidence: 99%
“…Earlier research papers have reported that the CNN, LSTM, and CNN-LSTM architectures for ECG authentication were able to achieve a classification accuracy of over 90% [ 35 ]. Although none of the proposed models offer a direct authentication approach that can be implemented without post-processing after classification, supervised DNN-based models, like classifiers, are commonly employed for authentication [ 36 ].…”
Section: Related Workmentioning
confidence: 99%
“…Using a BLSTM network, the suggested data-independent approach in [ 36 ] achieves a relatively better identification accuracy for each database. The proposed technique in [ 37 ] was tested using deep learning methods such as CNN and LSTM on self-collected databases S1 and S2, with the experimental results showing an EER% of 0–10.13% for the S2 database and the mixed S2 and S1 datasets, 0–5.31% for one-day enrollment, and 0.033–3.93% and 0–1.35% for two-day enrollment. The study in [ 38 ] proposed using an electrocardiogram and an ensemble of CNN and LSTM for personal identification, using the CU-ECG database created by Chosun University, which showed an accuracy greater than 90% in identifying individuals based on ECG signal characteristics.…”
Section: Related Workmentioning
confidence: 99%
“…The above structures CNN, LSTM, and CNN-LSTM for ECG authentication in previously written papers provided as classifi cation [22]. They reached more than 90% accuracy in classifi cation.…”
Section: Related Workmentioning
confidence: 99%